KEIKUTSERTAAN WANITA PASANGAN USIA SUBUR (PUS) DALAM PENGGUNAAN KB IUD - Tampubolon, Ida Lestari; Crystandy, Muhammad; Sikumbang, Fitry Anggreini (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
The high rate of population growth in Indonesia is due to the low coverage of family planning participants. One of them is the low use of IUD family planning which is only 4.7% due to lack of knowledge and understanding of the long-term benefits of IUD family planning. To determine the related factors to the fertile age women participation in the use of IUD Birth Control. The type of this research is analytical survey with cross sectional approach. This research was conducted at Kelurahan Sei Kera Hilir I of Medan Perjuangan Sub District Medan Kota. The sample of 87 people. The sampling was done by accidental sampling technique. Knowledge variables (p value = 0.000), parity (p value = 0.031), education (p value = 0.022), income (p value = 0.021) and husband support (p value = 0.000) has a relationship with the participation of fertile age women in the use of IUD Birth Control. Variables of husband's support and knowledge were the most influential variables in the use of IUD Birth Control. Shows that the most influential factor with the participation of fertile age women in the use of IUD Birth Control is husband's support and knowledge